Elucidating the effects of rapamycin and PF4 on the MNU induced female rats and human breast cancer cells (MCF-7) - Din, Tengku Ahmad Damitri Al-Astani Tengku (2015)
There is a strong evidence that tumour growth is not just a consequence of uncontrolled proliferation but also of reduced apoptosis. Bax and Bcl-2 are Bcl-2 family like apoptosis regulator. They function either as suppressor (Bcl-2) or a promoter (Bax) of apoptosis. As a member of the inhibitors of apoptosis (IAP), survivin is also a promoter of cellular proliferation and thus a key player in cancer progression. Beside, caspases also occupy a central role in maintaining cellular homeostasis. Therefore, this research aims to examine the apoptotic effects of Rapamycin and Platelet Factor 4 (PF4) on 1-methyl-1-nitrosourea (MNU)-induced mammary carcinoma through Bcl-2- survivin and caspase modulated pathways in female Sprague Dawley Rat (SDR) and in vitro MCF-7 breast cancer cell lines. One hundred 21 days old female SDR were given an intraperitoneal injection (IP) of MNU to induce breast cancer formation. When tumour size reached 14.5±0.5mm, intratumoural injections of the following interventions were given; Group 1 (preintervention control, n=20 and post-intervention control, n=20), Group 2 (Rapamycintreated, n=20), Group 3 (PF4-treated, n=20) and Group 4 (Rapamycin+PF4-treated, n=20). Tumour growth was then morphologically assessed using haematoxylin and eosin (H&E) and immunohistochemistry (IHC) utilizing pro-apoptosis (Bax) and antiapoptosis markers (Bcl-2), survivin and caspases-3,-6,-7,-8, and -9. Besides that, the MCF-7 cell line was used for in vitro assessment. Initially, half maximal inhibitory concentration (IC50) of each drug was determined. The MCF-7 cell lines were then exposed to Rapamycin and PF4 and Rapammycin+PF4 at IC50 concentrations, after which they were subjected to flow cytometry and Western blot analyses. Bax was significantly expressed at higher levels in the rapamycin-treated and Rapamycin+PF4- treated groups than controls (p<0.001). Besides, survivin was significantly downregulated in the PF4-treated and Rapamycin+PF4-treated group when compared to controls (p<0.001). On the other hand, Bcl-2 expression was found not to be significantly altred in all treatment groups. Caspase-3, was significantly expressed at higher levels in both PF4-treated and Rapamycin+PF4-treated groups than controls (p<0.001), as well as rapamycin-only group when compared to Rapamycin+PF4- treated and PF4-treated groups (both p<0.001). Apart from that, caspase-6 was also significantly expressed in Rapamycin-treated, PF4-treated and Rapamycin+PF4- treated than the control groups (p<0.001). Besides, either PF4 or Rapamycin+PF4 combination was associated with increased caspase-7 expression, compared to the controls (p<0.001). However, Rapamycin-treated group showed a significantly higher caspase-8 expression when compared to PF4-treated (p<0.05). For caspase-9, higher caspase-9 expression was observed in Rapamycin-treated group when compared to control, Rapamycin+PF4-treated and PF4-treated cohorts (p<0.001). The IC50 Rapamycin, PF4 and Rapamycin+PF4 were 0.4 μg/ml, 6 μg/ml and 0.4 μg/ml+1.0 μg/ml respectively. Rapamycin and PF4, on the other hand, were non-toxic to the normal HMEC cells. Furthermore, Rapamycin, PF4 and Rapamycin+PF4 induced a cell cycle arrest in MCF-7 cell lines at G0/G1, S and G0/G1 phases, respectively. Rapamycin, PF4 and Rapamycin+PF4 induced the upregulation of pro-apoptotic Bax and the downregulation of anti-apoptotic Bcl-2 and survivin. The expression levels of caspase-3 and caspase-8 were consistent in the treated group when compared with the control group. The expression of caspases -6, -7 and -9 protein were increased when treated with Rapamycin, Rapamycin + PF4 and PF4 when compared with the control group. In conclusion, this study provides new insights on the mechanistic properties of Rapamycin and PF4 as anti-cancer agents in breast cancer animal model and in vitro MCF-7 cell lines. The results lend support to the notion that apoptotic induction by Rapamycin and PF4 and was mediated by both the intrinsic and extrinsic pathways through the activation of caspase-9, caspase-3 and caspase-8 activation.